TAHAPAN PENGEMBANGAN MORAL: PERSPEKTIF BARAT DAN ISLAM (Telaah Terhadap Gagasan Thomas Lickona, Lawrence Kohlberg dan Al-Qur’an) - Iwan Kuswandi (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2020)
A decline in moral is among the impacts of technological development. For this reason, Thomas Lickona and Lawrence Kohlberg developed a concept of moral development, a concept which has also been discussed in the Holy Quran. Lickona stated that moral development stages are started with the ownership of moral knowledge (moral knowing) and move to moral feeling and moral action. Kohlberg stated that there are six stages in moral development. The stages are in three phases. First phase is called pre-conventional, which consists of stage 1 and stage 2. In this phase, people are more concerned about being right and wrong and getting reward or punishment. The next phase is called conventional phase, which consists of stage 3 and stage 4. In this level, people are more driven by internal motivation and how they are perceived by society. The final phase is post conventional phase, consisting of stage 5 and stage 6. In this level, people are able to independently interpret moral values and are driven by more universal values. The Quran divided the stages into some classes which are mentioned as ulul ilm (those of knowledge), ulin nuha (those of intelligence), ulil abshar (those of vision), ulil albab (those of understanding), ulil amri (those in authority), ulil aidi (those of strength) dan ulil azmi (those of determination).